Klasyfikacja konsumentów na rynku dóbr trwałego użytkowania w Polsce - Dziechciarz, Józef (Consumer classification on Polish durable goods market, 2006)
Paper shows the application of the cluster analysis framework for the durable goods market segmentation. The main goal was to classify consumers on Polish durable goods market and to identify the specific features of durable goods market in Poland. Therefore a questionnaire survey has been done, mainly on Lower Silesia area. Hence various clustering techniques were applied to analyze results of conducted research. Furthermore, an attempt to analyze classification results and to compare obtained consumer clusters of durable goods market segments was undertaken.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 389-396